Macrophyte species, composition, abundance and diversity in relation to some environmental factors in Upper Awash River basin, Ethiopia - Temesgen Tigab (International Journal of Science, Technology, Engineering and Mathematics)
The study assessed the species composition, distribution, and diversity of macrophytes in the Upper Awash River during dry and wet seasons across seven sampling sites from October 2019 to April 2020. Macrophytes were collected manually using the quadrat method, and environmental factors were measured in situ using YSI 556 multi probe system. Nutrients (SRP, TP, TN, Nitrate) were analyzed from water and sediment. A total of 26 macrophyte species from 15 families were identified, with low species diversity (H' = 2.56). Emergent macrophytes dominated (92%), followed by free-floating and rooted floating types (4% each). Canonical Correspondence Analysis (CCA) revealed that Nitrate, SRP, TP, and flow velocity significantly impacted macrophyte diversity and distribution. Cyperus articulatus L., Echinochloa colona L., Solanum incanum L., Pontederia crassipes, Persicaria senegalensis, Rorripa nasturtium aquaticum, Ipomoea aquatica and Phragmites mauritianus were almost restricted to sites where there was higher Nitrate, SRP and TP while Ludwigia spp., Sida schimperiana, Alternanthera sessilis, Lagarosiphon cordofanus, Brachiaria mutica, Juncus effuses, Ludwigia abyssinica, Cyperus latifolius, and Cyperus papyrus were limited to sites where there was higher DO,TN and Silt. Half of the macrophyte diversity was explained by environmental factors like nitrogen, phosphorus, and sediment texture. Further investigation of unexplained factors is needed for sustainable river management. This factor is crucial for developing strategies to enhance the river's ecological health and resource utilization.